Analyzing Lexical Density and Readability of Reading Texts in English Textbook “Stop Bullying Now” by Mahrukh Bashir - Miskiyah, Nafkhatul; Amalia, Taranindya Zulhi (Journal of English Teaching and Learning Issues, 2022)
The complexity of the text can be determined by lexical density and readability tests. Therefore, the purposes of this research are to find out the lexical density and readability of reading texts and the relevancy of them to the grade level of reading texts. This research took a descriptive qualitative method with library research. The subject is taken from the eleven reading texts in the English textbook "Stop Bullying Now" for eleventh grade. For analyzing data, the researcher used Ure formula and Flesch Reading Ease formula. The finding showed that 8 texts with a lexical density score >50% were categorized as quite-density and 3 texts were categorized as low-density. There are 5 levels of reading and only 4 texts which correspond to the students in senior high school. Based on the average analysis score, the texts are categorized as standard level and more appropriate for students in 8th-9th grade. In this study's data, lexical density and readability do not change considerably as text levels increase.